Nature-based interventions for individual, collective and planetary wellbeing: A protocol for a scoping review. - Jesse Blackburn; Afonso Pereira; Luke Jefferies; Andrew H Kemp; Amy Isham (PLoS ONE)
Nature-based interventions (NBIs) provide an opportunity to enhance individual wellbeing, improve community cohesion, and promote a culture of care for the environment. Several scoping reviews have attempted to catalogue the positive effects of NBIs on wellbeing, yet, these have typically focused on outcomes relating to individual wellbeing, thus restricting the assessment of the possible benefits of NBIs. Here we present a protocol for a scoping review that will synthesise the evidence relating to the impact of NBIs across a much broader range of domains with a focus on self (individual wellbeing), others (collective wellbeing) and nature (planetary wellbeing). This scoping review will also provide insight into the relative effectiveness of different types of NBIs at enhancing wellbeing across these domains and synthesise the underlying theory on which interventions have been developed and reported outcomes have been presented. A literature search for theses and peer-reviewed studies will be conducted on four databases (APAPsycINFO, Web of Science, Medline, and Scopus) and ProQuest Dissertations & Theses Global. Two independent reviewers will complete a two-stage screening process (title/abstract and full-text) using the Covidence platform. The protocol for this scoping review is registered with the Open Science Framework. Data extraction will focus on publication details, type of intervention, and wellbeing-related outcomes. Results will be reported in a scoping review following standardised guidelines relating to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses Extension for Scoping Reviews. This research will inform the design and delivery of NBI's across a wide range of sectors including health and social care, public policy, education, and community services, to ultimately promote human flourishing at scale.